Activation of implementation of information modelling technologies in the Russian construction industry - I. G. Lukmanova; E. V. Ukhalkin (Vestnik MGSU)
Introduction. In the Russian construction industry, the transition to information modelling technologies (BIM) is defined by the government as a priority task. Officially, the transition to BIM was planned in Russia in 2014, when the “Plan of phased introduction of information modelling technologies in the field of industrial and civil construction” was adopted, which is still, unfortunately, at the initial stage of implementation due to the following barriers: insufficiently developed regulatory and legal framework; shortage of BIM specialists; high cost of software (mostly foreign), as well as the lack of tested methods of economic justification of the feasibility of the application of BIM. The article analyzes the world experience of the countries, which have successfully implemented BIM in production, and reveals the main reasons for the unacceptably low rates of BIM usage in the construction industry. The authors of the article offer the algorithm of activation of introduction of BIM in construction, algorithm of actions for software choosing and a technique for calculation of the expected economic effect of the use of information modelling technologies in investment and building projects realization. The final results of testing in practice the developed methodological tools are given.Materials and methods. The research is based on system, process and situational approaches, methods of comparative and factor analysis of the results of foreign and domestic experience, as well as methods of economic-mathematical and graphic modelling. This methodological set allowed assessing the influence of factor space on the processes of applying BIM at the stages of the life cycle of ICP and to propose an algorithm of actions to intensify the implementation of BIM in the domestic construction industry.Results. The analysis of the results and outcomes of the use of BIM in Russia and in developed foreign countries, carried out by the authors, made it possible to establish the lag and identify its main causes, as well as outline ways to eliminate them.Conclusions. The proposed algorithms, economic and mathematical model for calculating the expected economic effect will enable Russian construction companies to reasonably approach the process of introducing BIM in the implementation of investment and construction projects.